Buried bottom interface defect passivated trans-perovskite solar cell and preparation method thereof

By introducing organic compounds containing hydrophobic long carbon chains, positively charged amino groups and negatively charged halogen functional groups into perovskite solar cells as interface modification layers, the problem of buried interface defects in perovskite solar cells is solved. The photoelectric performance and stability of the battery are significantly improved.

CN119497497AActive Publication Date: 2025-02-21烟台哈尔滨工程大学研究院
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411614128.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-21
Estimated Expiration
2044-11-13

AI Technical Summary

Technical Problem

The battery performance and stability of perovskite solar cells are affected by defects in the buried interface, which is difficult to effectively adjust and improve.

Method used

Organic compounds containing hydrophobic long carbon chains, positively charged amino groups and negatively charged halogen functional groups are introduced as interface modification layers to modify the interface between the hole transport layer and the light absorbing layer of the perovskite layer.

Benefits of technology

Through the introduction of the interface modification layer, the photoelectric performance of the perovskite film and the energy conversion efficiency and long-term stability of solar cell devices are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119497497A_ABST
    Figure CN119497497A_ABST
Patent Text Reader

Abstract

The invention discloses a bottom-buried interface defect-passivated trans-perovskite solar cell and a preparation method of the bottom-buried interface defect-passivated trans-perovskite solar cell, and belongs to the technical field of solar cells. An interface modification layer is arranged between a hole transport layer and a perovskite light absorption layer of the trans-perovskite solar cell; the material of the interface modification layer is an organic compound containing a hydrophobic long carbon chain, a positively charged amino group and a negatively charged halogen functional group at the same time; the hydrophobic long carbon chain in the material of the interface modification layer can enhance the stability; the positively charged amino group can be fixed on the grain boundary and the surface of the perovskite film by occupying the point passivation vacancy of the cubic octahedron so as to compensate the loss on the surface of the film, and the negative electricity defect in the perovskite is passivated through an ionic bond or a hydrogen bond; the negatively charged halogen functional group can slow down the crystallinity in the film forming process, increase the size of perovskite, and improve the photoelectric property of the perovskite film and the overall energy conversion efficiency, moisture resistance and long-term stability of the device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of solar cells, and in particular relates to an inverted perovskite solar cell with buried interface defect passivation and a preparation method thereof. Background Art

[0002] After years of development, photovoltaic power generation technology has made significant progress in terms of cost and photoelectric conversion efficiency. As the third generation of solar cells, perovskite solar cells have attracted widespread attention due to their low cost, low-temperature preparation and high photoelectric conversion efficiency. Compared with traditional silicon-based solar cells, perovskite solar cells not only have low material costs, but also simple manufacturing processes and can be prepared at low temperatures, thereby reducing production costs. These advantages make perovskite solar cells show great potential in the field of renewable energy. In addition, the excellent optical and electrical properties of perovskite materials give them significant advantages in photoelectric conversion efficiency. Studies have shown that the photoelectric conversion efficiency of perovskite solar cells has reached a level comparable to or even higher than that of traditional silicon-based cells under laboratory conditions, and the efficiency of single-junction perovskite solar cells has exceeded 26%. With the continuous advancement and optimization of related technologies, the performance and stability of perovskite solar cells will be further improved, which will pave the way for their large-scale commercial application. Driven by the "dual carbon" goal, the development of high-efficiency and low-cost photovoltaic technology represented by perovskite solar cells will not only help reduce dependence on fossil fuels, but also significantly reduce carbon dioxide emissions and achieve sustainable development goals. Therefore, perovskite solar cells have important strategic significance and application prospects in the future development of clean energy.

[0003] The quality of perovskite solar cells depends largely on the quality of the perovskite light-absorbing layer. As a defect passivation method, interface engineering is often used to passivate the surface defect states of the perovskite light-absorbing layer, reduce carrier non-radiative recombination, defect passivation, and improve interface contact. The buried interface is more difficult to adjust than the exposed upper surface of the prepared perovskite layer, but it is of great importance. The grains of the perovskite layer grow from bottom to top. Here, a simple and feasible treatment method is developed to modify the buried interface of the perovskite layer to obtain a perovskite light-absorbing layer with more complete grain growth and fewer defect states, while making the film formation more uniform and the perovskite layer of better quality. Based on this, it is crucial to develop a buried interface modification method to optimize perovskite solar cells. Summary of the invention

[0004] In order to solve the above technical problems, the present invention proposes a buried interface defect passivated inverted perovskite solar cell and a preparation method thereof. The present invention introduces an organic compound containing a hydrophobic long carbon chain, a positively charged amino group and a negatively charged halogen functional group to regulate the interface between perovskite layers, which can effectively improve the photoelectric performance of the perovskite film and the energy conversion efficiency and long-term stability of the perovskite solar cell device.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] One of the technical solutions of the present invention:

[0007] An inverse perovskite solar cell with buried interface defect passivation, wherein an interface modification layer is provided between a hole transport layer and a perovskite light absorbing layer;

[0008] The material of the interface modification layer is an organic compound containing a hydrophobic long carbon chain, a positively charged amino group and a negatively charged halogen functional group.

[0009] Preferably, the material of the interface modification layer is cetyltrimethylammonium bromide (CTAB) or cetyltrimethylammonium chloride (CTAC).

[0010] The present invention introduces an interface modification layer between the hole transport layer and the perovskite light absorbing layer of the perovskite solar cell, which not only enhances the conductivity of the hole transport layer, but also optimizes the lower interface of the perovskite light absorbing layer, improves the perovskite crystallization process, reduces the surface roughness of the perovskite light absorbing layer, and reduces interface defects, thereby achieving the purpose of effectively enhancing the photoelectric performance and long-term stability of the battery device.

[0011] Preferably, the buried interface defect passivated inverted perovskite solar cell comprises, from bottom to top: a transparent conductive substrate, a hole transport layer, an interface modification layer, a perovskite light absorption layer, an electron transport layer, a BCP buffer layer and a top metal electrode.

[0012] Preferably, the transparent conductive substrate comprises indium tin oxide (ITO) or fluorine-doped tin oxide (FTO); and / or

[0013] The material of the hole transport layer includes one of MeO-2PACz ((2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl)phosphonic acid), PEDOT:PSS (poly(3,4-ethylenedioxythiophene):poly(styrenesulfonic acid)) and Me-4PACz ([4-(3,6-dimethoxy-9H-carbazole-9-yl)butyl]phosphonic acid); and / or

[0014] The material structure of the perovskite light absorbing layer is ABX 3 , where A is CH 3 NH3 + (MA + ), NH 2 CH=NH 2 + (FA + ) and Cs + One of the following; B is Pb 2+ and Sn 2+ One of the following; X is Cl - Br - and I - One of; and / or

[0015] The materials of the electron transport layer are PCBM and fullerene (such as C 60 )

[0016] The transparent conductive substrate of the present invention has the characteristics of high conductivity, high visible light transmittance, high mechanical hardness and good chemical stability; the hole transport layer material of the present invention has the characteristics of good conductivity, high light transmittance, low temperature annealing and good energy level matching with the perovskite layer material; the perovskite light absorption layer material of the present invention has the characteristics of large absorption coefficient, adjustable band gap, simple synthesis method and high conversion efficiency; the electron layer transport material of the present invention has the characteristics of suitable energy level, high electron transmission ability, simple film forming process and can reduce surface charge recombination. Compared with the prior art, the present invention adopts interface modified organic compounds to enhance the conductivity of the hole transport layer and modify the lower surface of the perovskite light absorption layer, improves the perovskite crystallization process, reduces the surface roughness of the perovskite light absorption layer, and passivates and reduces interface defects, so as to achieve the purpose of enhancing the photoelectric performance and long-term stability of the battery device. The cell efficiency, moisture resistance and long-term stability of the trans-perovskite solar cell modified by the above-mentioned organic compound of the present invention are significantly higher than those of the trans-perovskite solar cell not modified by the organic compound.

[0017] Preferably, the BCP buffer layer is bathocuproine (BCP); and / or

[0018] The material of the top metal electrode is one of gold (Au), silver (Ag), copper (Cu) and aluminum (Al).

[0019] Preferably, the thickness of the transparent conductive substrate is 80-100nm, the thickness of the hole transport layer is 10-20nm, the thickness of the perovskite light absorption layer is 400-500nm, the thickness of the electron transport layer is 20-40nm, and the thickness of the top metal electrode is 80-100nm. The transparent conductive substrate (such as ITO or FTO) needs to have high transmittance to allow sunlight to pass through, and good conductivity to transmit current. The thickness of the substrate will affect its conductivity and mechanical strength. Too thick will increase the cost and reduce the transmittance, while too thin may affect the conductivity and durability. The hole transport layer needs to form a good heterojunction contact interface with the perovskite light absorption layer to reduce the potential barrier in the hole transport process. The thickness of the hole transport layer will affect its conductivity and the filling factor of the battery. Too thick a hole transport layer will increase optical loss and electrical loss, while too thin a hole transport layer may lead to insufficient hole transport. The thickness of the perovskite light absorption layer directly affects light absorption and carrier generation. Increasing the thickness of the perovskite light absorption layer will increase the optical loss and electrical loss. The degree can enhance the absorption of incident light, but at the same time it will also increase the defects in the film, resulting in an increase in non-radiative recombination and affecting the photoelectric conversion efficiency. Therefore, it is necessary to find a balance point to achieve the best light absorption and carrier capture ability; the electron transport layer needs to form an electron-selective contact with the perovskite light-absorbing layer to improve the electron extraction efficiency and prevent holes from migrating toward the cathode. The thickness of the electron transport layer will affect the electron transmission efficiency and the open circuit voltage of the battery. An overly thick electron transport layer may increase the series resistance of the battery and reduce performance; the thickness of the top metal electrode will affect its conductivity and stability. An overly thick top metal electrode will increase the cost and block light, while an overly thin top metal electrode may affect its conductivity and durability. The present invention uses an organic compound containing a hydrophobic long carbon chain, a positively charged amino group and a negatively charged halogen functional group for interface modification, without changing the original device structure of the perovskite solar cell.

[0020] The second technical solution of the present invention:

[0021] The present invention also provides a method for preparing the buried interface defect passivated inverse perovskite solar cell, comprising the following steps:

[0022] 1) Preparing a hole transport layer on a transparent conductive substrate;

[0023] 2) preparing an interface modification layer on the hole transport layer;

[0024] 3) preparing a perovskite light absorbing layer on the interface modification layer;

[0025] 4) preparing an electron transport layer on the perovskite light absorbing layer;

[0026] 5) preparing a BCP buffer layer on the electron transport layer;

[0027] 6) Preparing a top metal electrode on the BCP buffer layer.

[0028] Preferably, before preparing the hole transport layer on the transparent conductive substrate, the transparent conductive substrate is first treated, and the specific method is as follows: the transparent conductive substrate is cleaned with a cleaning agent, dried, and subjected to ultraviolet ozone treatment.

[0029] Preferably, in the process of treating the transparent conductive substrate, the cleaning agent is at least one of deionized water, anhydrous ethanol, isopropyl alcohol (IPA) and acetone.

[0030] Preferably, in step 1), the method for preparing the hole transport layer on the transparent conductive substrate is: coating the material of the hole transport layer on the transparent conductive substrate and performing annealing treatment.

[0031] Preferably, in step 1), the annealing temperature is 100-140° C. and the time is 10-30 min.

[0032] More preferably, in step 1), the annealing temperature is 120° C. and the time is 20 min.

[0033] Preferably, in step 2), the method for preparing the interface modification layer on the hole transport layer is: dissolving the material of the interface modification layer in an organic solvent, coating the layer on the hole transport layer, and performing annealing treatment.

[0034] Preferably, in step 2), the annealing temperature is 50-70° C. and the time is 5-10 min.

[0035] More preferably, in step 2), the annealing temperature is 70° C. and the time is 5 min.

[0036] Preferably, in step 2), after the material of the interface modification layer is dissolved in an organic solvent, the concentration of the material of the interface modification layer in the obtained solvent is 0.4-2 mg / mL;

[0037] The organic solvent includes at least one of dimethyl sulfoxide (DMSO), N,N-dimethylacetamide (DMF), isopropyl alcohol (IPA) and chlorobenzene (CB).

[0038] More preferably, in step 2), after the material of the interface modification layer is dissolved in an organic solvent, the concentration of the material of the interface modification layer in the obtained solution is 0.4 mg / mL, 0.7 mg / mL, 1 mg / mL or 2 mg / mL;

[0039] Preferably, in step 3), the method for preparing the perovskite light-absorbing layer on the interface modification layer is: preparing a perovskite precursor solution by dissolving iodide or bromide and lead iodide in an organic solvent, spin-coating the prepared perovskite precursor solution onto the interface modification layer, and performing annealing treatment; and / or

[0040] The organic solvent includes at least one of DMSO, DMF, IPA and CB.

[0041] Preferably, in step 3), the annealing temperature is 100-120° C. and the time is 10-30 min.

[0042] More preferably, in step 3), the annealing temperature is 100° C. and the time is 10 min.

[0043] Preferably, in step 4), the method for preparing the electron transport layer on the perovskite light absorbing layer is: dissolving the electron transport layer material in a solvent, and spin coating or evaporating the material on the perovskite light absorbing layer.

[0044] Preferably, in step 5), the method for preparing the BCP buffer layer on the electron transport layer is: dissolving BCP in a solvent and spin coating the BCP on the electron transport layer.

[0045] Preferably, in step 6), a top metal electrode is prepared on the BCP buffer layer by vacuum evaporation.

[0046] Preferably, the solvents in step 4) and step 5) are independently selected from ethanol (CH 3 CH 2 OH), isopropyl alcohol (IPA), n-butyl alcohol (CH 3 (CH 2 ) 3 OH), chlorobenzene (CB), toluene (C 7 H 8 ) and water (H 2 O) one of them.

[0047] The principle of the present invention is:

[0048] Compared with the prior art, the present invention has the following advantages and technical effects:

[0049] Compared with the existing methods of interface modification of perovskite films, the present invention uses organic compounds containing hydrophobic long carbon chains, positively charged amino groups and negatively charged halogen functional groups to modify the interface between the upper surface of the hole transport layer and the lower surface of the perovskite light absorbing layer.

[0050] The hydrophobic long carbon chain in the organic compound of the present invention can enhance stability; the positively charged amino group can occupy the cubic octahedral point passivation vacancy and be fixed on the grain boundary and surface of the perovskite film to compensate for the loss on the film surface, and passivate the negatively charged defects in the perovskite through ionic bonds or hydrogen bonds; the negatively charged halogen functional group can slow down the crystallinity in the film forming process and increase the size of the perovskite. In addition, the intervention of the negatively charged halogen functional group can modify the energy level so that the battery can obtain a higher open circuit voltage. Other studies have shown that the surface of the perovskite film does not necessarily reach a thermal dynamic stable state immediately after annealing. Due to the mismatch between the thermal expansion coefficients of the perovskite and the substrate, the residual strain of the lower interface will be generated. When the annealed perovskite film is cooled to room temperature, the lattice distortion occurs, resulting in an increase in grain boundary defects, which will accelerate the degradation of the perovskite film, increase non-radiative recombination, and reduce the photoelectric performance of the battery. The lattice mismatch between perovskite and substrate during the annealing process can lead to the generation of residual stress. Long carbon chains can improve this contact, thereby reducing the residual stress of perovskite, which is conducive to the preparation of higher quality perovskite solar cells. In this context, the zwitterionic structure CTAB / CTAC with positive and negative ion separation has the advantage of adaptively selecting defects with opposite charges for passivation, and is not restricted by the complex surface defect composition or distribution. In addition, the introduction of CTAB / CTAC can improve the roughness and conductivity of the hole transport layer. In summary, CTAB / CTAC plays a role in improving the perovskite light absorption layer and enhancing the conductivity of the hole transport layer.

[0051] The inverted perovskite solar cell prepared by using the material and preparation method of the present invention improves the photoelectric performance of the perovskite film and the energy conversion efficiency, moisture resistance and long-term stability of the entire device.

[0052] The preparation method of the present invention is simple, efficient, reliable, and has good stability, and meets actual production requirements. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:

[0054] Figure 1 A schematic diagram of the structure of an inverted perovskite solar cell provided in Example 1, wherein: 1-transparent conductive substrate, 2-hole transport layer, 3-interface modification layer, 4-perovskite light absorption layer, 5-electron transport layer, 6-BCP buffer layer, 7-top metal electrode;

[0055] Figure 2 The structural formula of the buried interface modified defect passivation material;

[0056] Figure 3The JV curves of the inverse perovskite solar cells obtained in Comparative Example 1 and Example 2;

[0057] Figure 4 The SEM images of the inverse perovskite solar cells obtained in Comparative Example 1 and Example 2;

[0058] Figure 5 The water contact angle images of the hole transport layer of the inverse perovskite solar cell obtained in Comparative Example 1 and Example 2;

[0059] Figure 6 It is a comparison chart of the long-term stability test results of the unpackaged devices obtained in Comparative Example 1 and Example 5 at room temperature. DETAILED DESCRIPTION

[0060] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0061] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0062] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0063] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0064] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0065] Unless otherwise specified, the room temperature in the present invention is 25±2°C.

[0066] All raw materials used in the examples of the present invention are commercially available.

[0067] The present invention provides a perovskite solar cell (schematic diagram of the structure is shown in Figure 1 ), from bottom to top, includes: a transparent conductive substrate 1, a hole transport layer 2, an interface modification layer 3, a perovskite light absorption layer 4, an electron transport layer 5, a BCP buffer layer 6 and a top metal electrode 7.

[0068] The structural formula of the buried interface modification defect passivation material (i.e., the material of the interface modification layer) of the present invention is shown in Figure 2 .

[0069] It should be pointed out that the parts not described in detail in the present invention are all conventional operating means in the art, for example, specific methods such as spin coating, evaporation or vacuum evaporation are all completed by conventional methods.

[0070] The technical solution of the present invention is further illustrated by the following embodiments.

[0071] Example 1

[0072] 1) Treating the transparent conductive substrate 1: using detergent (Tide detergent, the same below), deionized water and IPA in sequence to ultrasonically clean the ITO transparent conductive electrode with a thickness of 90 nm for 20 minutes, and then using ultraviolet ozone treatment for 15 minutes, waiting for subsequent use;

[0073] 2) Preparation of hole transport layer 2: Spin coating the PEDOT:PSS solution on the surface of the ITO substrate pre-treated with UV ozone to form a uniform film, wherein the spin coating speed is 3000 rpm, the spin coating time is 30 s, and then annealing is performed to completely remove the remaining solution, wherein the annealing temperature is 120° C., the annealing time is 20 min, and after cooling to room temperature, the film is transferred to a glove box filled with nitrogen to obtain a hole transport layer 2 with a thickness of 15 nm;

[0074] 3) preparing the interface modification layer 3: uniformly dropping 50 μL of a CTAB solution dissolved in IPA onto the hole transport layer 2, wherein the solution concentration is 0.4 mg / mL (denoted as 0.4-CTAB), and then spin coating the hole transport layer 2 at 4000 rpm for 30 s, and then annealing at 70° C. for 5 min to remove the residual solvent, thereby obtaining the interface modification layer 3;

[0075] 4) Preparation of perovskite light absorbing layer 4: 1.2M lead iodide (PbI 2 ) and 1.2 M methylammonium iodide (MAI) were dissolved in a mixed solution of 900 μL DMF and 100 μL DMSO to prepare MAPbI3 Perovskite precursor solution, 65 μL of perovskite precursor solution was spin-coated on the interface modification layer 3, wherein the spin-coating speed was 4000 rpm and the spin-coating time was 30 s. During the spin-coating (i.e., spin coating) process, 200 μL of CB was quickly dripped before the surface became turbid, and finally the prepared film was placed on a hot plate for annealing, wherein the annealing temperature was 100 ° C and the annealing time was 10 min, to obtain a perovskite light absorption layer 4 with a thickness of 450 nm;

[0076] 5) Preparation of electron transport layer 5: After the device is cooled to room temperature, a PCBM solution (20 mg / mL) dissolved in CB is spin-coated on the prepared perovskite light absorption layer 4 at a speed of 3000 rpm for 30 seconds to obtain an electron transport layer 5 with a thickness of 30 nm;

[0077] 6) Preparing a BCP buffer layer 6: Spin-coating a BCP solution (0.5 mg / mL) dissolved in IPA on the prepared electron transport layer 5 at a speed of 8000 rpm for 30 seconds to obtain a BCP buffer layer 6;

[0078] 7) Preparation of top metal electrode 7: At 2×10 -4 Under a pressure of pa, Ag is vacuum deposited on the prepared BCP buffer layer 6 to obtain a top metal electrode 7 (the thickness of the top metal electrode 7 is 100 nm), thereby obtaining an inverse perovskite solar cell with buried interface defect passivation.

[0079] Example 2

[0080] 1) treating the transparent conductive substrate 1: using detergent, deionized water and IPA in sequence to ultrasonically clean the ITO transparent conductive electrode with a thickness of 90 nm for 20 minutes, and then using ultraviolet ozone treatment for 15 minutes, and waiting for subsequent use;

[0081] 2) Preparation of hole transport layer 2: Spin coating the PEDOT:PSS solution on the surface of the ITO transparent conductive substrate pre-treated with UV ozone to form a uniform film, wherein the spin coating speed is 3000 rpm, the spin coating time is 30 s, and then annealing is performed to completely remove the remaining solution, wherein the annealing temperature is 120° C., the annealing time is 20 min, and after cooling to room temperature, the film is transferred to a glove box filled with nitrogen to obtain a hole transport layer 2 with a thickness of 15 nm;

[0082] 3) preparing the interface modification layer 3: uniformly dropping 50 μL of a CTAB solution dissolved in IPA onto the hole transport layer 2, wherein the solution concentration is 0.7 mg / mL (referred to as 0.7-CTAB), and then spin coating the hole transport layer 2 at 4000 rpm for 30 s, and then annealing at 70° C. for 5 min to remove the residual solvent, thereby obtaining the interface modification layer 3;

[0083] 4) Preparation of perovskite light absorbing layer 4: 1.2M PbI 2 MAPbI was prepared by dissolving 1.2 M MAI in a mixed solution of 900 μL DMF and 100 μL DMSO. 3 Perovskite precursor solution, 65 μL of perovskite precursor solution is dropped on the interface modification layer 3, wherein the spin coating speed is 4000 rpm, and the spin coating time is 30 s. During the spin coating process, 200 μL of CB is quickly dropped before the surface becomes turbid. Finally, the prepared film is placed on a hot plate for annealing, wherein the annealing temperature is 100 ° C, and the annealing time is 10 min, to obtain a perovskite light absorption layer 4 with a thickness of 450 nm;

[0084] 5) Preparation of electron transport layer 5: After the device is cooled to room temperature, a PCBM solution (20 mg / mL) dissolved in CB is spin-coated on the prepared perovskite light absorption layer 4 at a speed of 3000 rpm for 30 seconds to obtain an electron transport layer 5 with a thickness of 30 nm;

[0085] 6) Preparing a BCP buffer layer 6: Spin-coating a BCP solution (0.5 mg / mL) dissolved in IPA on the prepared electron transport layer 5 at a speed of 8000 rpm for 30 seconds to obtain a BCP buffer layer 6;

[0086] 7) Preparation of top metal electrode 7: At 2×10 -4 Under a pressure of pa, Ag is vacuum deposited on the prepared BCP buffer layer 6 to obtain a top metal electrode 7 (the thickness of the top metal electrode 7 is 100 nm), thereby obtaining an inverse perovskite solar cell with buried interface defect passivation.

[0087] Example 3

[0088] 1) treating the transparent conductive substrate 1: using detergent, deionized water and isopropyl alcohol (IPA) to ultrasonically clean the ITO transparent conductive electrode with a thickness of 90 nm for 20 minutes, and then using ultraviolet ozone treatment for 15 minutes, and waiting for subsequent use;

[0089] 2) Preparation of hole transport layer 2: Spin coating the PEDOT:PSS solution on the surface of the ITO transparent conductive substrate pre-treated with UV ozone to form a uniform film, wherein the spin coating speed is 3000 rpm, the spin coating time is 30 s, and then annealing is performed to completely remove the remaining solution, wherein the annealing temperature is 120° C., the annealing time is 20 min, and after cooling to room temperature, the film is transferred to a glove box filled with nitrogen to obtain a hole transport layer 2 with a thickness of 15 nm;

[0090] 3) preparing the interface modification layer 3: uniformly dropping 50 μL of a CTAB solution dissolved in IPA onto the hole transport layer 2, wherein the solution concentration is 1 mg / mL (denoted as 1-CTAB), and then spin coating the hole transport layer 2 at 4000 rpm for 30 s, and then annealing at 70° C. for 5 min to remove the residual solvent, thereby obtaining the interface modification layer 3;

[0091] 4) Preparation of perovskite light absorbing layer 4: 1.2M PbI 2 MAPbI was prepared by dissolving 1.2 M MAI in a mixed solution of 900 μL DMF and 100 μL DMSO. 3 Perovskite precursor solution, 65 μL of perovskite precursor solution is dropped on the interface modification layer 3, wherein the spin coating speed is 4000 rpm, and the spin coating time is 30 s. During the spin coating process, 200 μL of CB is quickly dropped before the surface becomes turbid. Finally, the prepared film is placed on a hot plate for annealing, wherein the annealing temperature is 100 ° C, and the annealing time is 10 min, to obtain a perovskite light absorption layer 4 with a thickness of 450 nm;

[0092] 5) Preparation of electron transport layer 5: After the device is cooled to room temperature, a PCBM solution (20 mg / mL) dissolved in CB is spin-coated on the prepared perovskite light absorption layer 4 at a speed of 3000 rpm for 30 seconds to obtain an electron transport layer 5 with a thickness of 30 nm;

[0093] 6) Preparing a BCP buffer layer 6: Spin-coating a BCP solution (0.5 mg / mL) dissolved in IPA on the prepared electron transport layer 5 at a speed of 8000 rpm for 30 seconds to obtain a BCP buffer layer 6;

[0094] 7) Preparation of top metal electrode 7: At 2×10 -4 Under a pressure of pa, Ag is vacuum deposited on the prepared BCP buffer layer 6 to obtain a top metal electrode 7 (the thickness of the top metal electrode 7 is 100 nm), thereby obtaining an inverse perovskite solar cell with buried interface defect passivation.

[0095] Example 4

[0096] 1) treating the transparent conductive substrate 1: using detergent, anhydrous ethanol and acetone to ultrasonically clean the ITO transparent conductive electrode with a thickness of 100 nm for 20 minutes, and then using ozone to treat for 15 minutes, and waiting for subsequent use;

[0097] 2) Preparation of hole transport layer 2: In a nitrogen-filled glove box, a MeO-2PACz solution (2 mg / mL MeO-2PACz dissolved in anhydrous ethanol) was spin-coated on the surface of an ITO transparent conductive substrate pre-treated with UV ozone to form a uniform film, wherein the spin coating speed was 4000 rpm and the spin coating time was 30 s, followed by annealing to completely remove the remaining anhydrous ethanol, wherein the annealing temperature was 100° C. and the annealing time was 10 min. After cooling to room temperature, a hole transport layer 2 with a thickness of 10 nm was obtained;

[0098] 3) preparing the interface modification layer 3: uniformly dropping 50 μL of a CTAC solution dissolved in IPA onto the hole transport layer 2, wherein the solution concentration is 2 mg / mL, and then spin coating the hole transport layer 2 at 4000 rpm for 30 s, and then annealing at 70° C. for 3 min to remove the residual solvent, thereby obtaining the interface modification layer 3;

[0099] 4) Preparation of perovskite light absorbing layer 4: 1.2M PbI 2 MAPbI was prepared by dissolving 1.2 M MAI in a mixed solution of 900 μL IPA and 100 μL CB. 3 Perovskite precursor solution, 50 μL of the perovskite precursor solution was spin-coated on the interface modification layer 3, wherein the spin-coating speed was 3500 rpm and the spin-coating time was 30 s. During the spin-coating (i.e., spin coating) process, 200 μL of CB was quickly dripped before the surface became turbid, and finally the prepared film was placed on a hot plate for annealing, wherein the annealing temperature was 110°C and the annealing time was 10 min, to obtain a perovskite light-absorbing layer 4 with a thickness of 500 nm;

[0100] 5) Preparation of electron transport layer 5: After the device is cooled to room temperature, a PCBM solution (20 mg / mL) dissolved in CB is spin-coated on the prepared perovskite light absorption layer 4 at a speed of 4000 rpm for 30 seconds to obtain an electron transport layer 5 with a thickness of 20 nm;

[0101] 6) Preparation of BCP buffer layer 6: Dissolve in CH 3 CH 2 The BCP solution of OH (0.5 mg / mL) was spin-coated on the prepared electron transport layer 5 at a speed of 8000 rpm for 30 s to obtain a BCP buffer layer 6;

[0102] 7) Preparation of top metal electrode 7: At 2×10 -4 Under a pressure of pa, Au is vacuum deposited on the prepared BCP buffer layer 6 to obtain a top metal electrode 7 (the thickness of the top metal electrode 7 is 100 nm), thereby obtaining an inverted perovskite solar cell with buried interface defect passivation.

[0103] Example 5

[0104] 1) treating the transparent conductive substrate 1: using detergent, anhydrous ethanol and acetone to ultrasonically clean the FTO transparent conductive electrode with a thickness of 80 nm for 20 minutes, and then using ultraviolet ozone treatment for 15 minutes, and waiting for subsequent use;

[0105] 2) Preparation of hole transport layer 2: In a nitrogen-filled glove box, a Me-4PACz solution (2 mg / mL Me-4PACz dissolved in anhydrous ethanol) was spin-coated on the surface of a FTO transparent conductive substrate previously treated with UV ozone to form a uniform film, wherein the spin coating speed was 4000 rpm and the spin coating time was 30 s, followed by annealing to completely remove the remaining anhydrous ethanol, wherein the annealing temperature was 100° C. and the annealing time was 10 min. After cooling to room temperature, a hole transport layer 2 with a thickness of 15 nm was obtained;

[0106] 3) preparing the interface modification layer 3: uniformly dropping 50 μL of CTAC solution dissolved in IPA on the hole transport layer 2, wherein the solution concentration is 2 mg / mL, and then spin coating on the hole transport layer 2 at 4000 rpm for 30 s, and then annealing at 70° C. for 3 min to remove the residual solvent, thereby obtaining the interface modification layer 3;

[0107] 4) Preparation of perovskite light absorbing layer 4: 1.2M PbI 2 MAPbI was prepared by dissolving 1.2 M MAI in a mixed solution of 900 μL DMF and 100 μL DMSO. 3 Perovskite precursor solution, 50 μL of the perovskite precursor solution is spin-coated on the interface modification layer 3, wherein the spin-coating speed is 3500 rpm and the spin-coating time is 30 s. During the spin-coating (i.e., spin coating) process, 200 μL of CB is quickly dripped before the surface becomes turbid, and finally the prepared film is placed on a hot plate for annealing, wherein the annealing temperature is 100 ° C and the annealing time is 10 min, to obtain a perovskite light-absorbing layer 4 with a thickness of 500 nm;

[0108] 5) Preparation of electron transport layer 5: After the device is cooled to room temperature, C dissolved in CB 60 The solution (20 mg / mL) was spin-coated on the prepared perovskite light absorbing layer 4 at a speed of 4000 rpm for 30 s to obtain an electron transport layer 5 with a thickness of 20 nm;

[0109] 6) Preparing a BCP buffer layer 6: Spin-coating a BCP solution (0.5 mg / mL) containing CB on the prepared electron transport layer 5 at a speed of 8000 rpm for 30 seconds to obtain a BCP buffer layer 6;

[0110] 7) Preparation of top metal electrode 7: At 2×10 -4 Under a pressure of pa, the top metal electrode 7Cu is vacuum deposited on the prepared BCP buffer layer 6 (the thickness of the top metal electrode 7 is 100nm) to obtain an inverse perovskite solar cell with buried interface defect passivation.

[0111] Example 6

[0112] 1) treating the transparent conductive substrate 1: using detergent, deionized water and IPA in sequence to ultrasonically clean the ITO transparent conductive electrode with a thickness of 80 nm for 20 minutes, and then using ultraviolet ozone treatment for 15 minutes, and waiting for subsequent use;

[0113] 2) Preparation of hole transport layer 2: Spin coating the PEDOT:PSS solution on the surface of the ITO transparent conductive substrate pre-treated with UV ozone to form a uniform film, wherein the spin coating speed is 2500 rpm, the spin coating time is 30 s, and then annealing is performed to completely remove the remaining solution, wherein the annealing temperature is 100° C., the annealing time is 30 min, and after cooling to room temperature, the film is transferred to a glove box filled with nitrogen to obtain a hole transport layer 2 with a thickness of 20 nm;

[0114] 3) preparing the interface modification layer 3: uniformly dropping 50 μL of a CTAB solution dissolved in IPA onto the hole transport layer 2, wherein the solution concentration is 1 mg / mL (denoted as 1-CTAB), and then spin coating the hole transport layer 2 at 4000 rpm for 30 s, and then annealing at 50° C. for 10 min to remove the residual solvent, thereby obtaining the interface modification layer 3;

[0115] 4) Preparation of perovskite light absorbing layer 4: 1.2M SnI 2 (tin iodide) and 1.2 M MAI were dissolved in a mixed solution of 900 μL DMF and 100 μL DMSO to prepare MASnI 3 Perovskite precursor solution: 65 μL of perovskite precursor solution is dropped on the interface modification layer 3, wherein the spin coating speed is 3500 rpm and the spin coating time is 30 s. During the spin coating process, 200 μL of CB is quickly dropped before the surface becomes turbid. Finally, the prepared film is placed on a hot plate for annealing, wherein the annealing temperature is 120°C and the annealing time is 10 min, to obtain a perovskite light absorption layer 4 with a thickness of 500 nm.

[0116] 5) Preparation of electron transport layer 5: After the device is cooled to room temperature, a PCBM solution (20 mg / mL) dissolved in CB is spin-coated on the prepared perovskite light absorption layer 4 at a speed of 2000 rpm for 30 seconds to obtain an electron transport layer 5 with a thickness of 40 nm;

[0117] 6) Preparing a BCP buffer layer 6: Spin-coating a BCP solution (0.5 mg / mL) dissolved in IPA on the prepared electron transport layer 5 at a speed of 8000 rpm for 30 seconds to obtain a BCP buffer layer 6;

[0118] 7) Preparation of top metal electrode 7: At 2×10 -4 Under a pressure of pa, Ag is vacuum deposited on the prepared BCP buffer layer 6 to obtain a top metal electrode 7 (the thickness of the top metal electrode 7 is 80 nm), thereby obtaining an inverse perovskite solar cell with buried interface defect passivation.

[0119] Example 7

[0120] 1) treating the transparent conductive substrate 1: using detergent, deionized water and IPA in sequence to ultrasonically clean the ITO transparent conductive electrode with a thickness of 90 nm for 20 minutes, and then using ultraviolet ozone treatment for 15 minutes, and waiting for subsequent use;

[0121] 2) Preparation of hole transport layer 2: Spin coating the PEDOT:PSS solution on the surface of the ITO transparent conductive substrate pre-treated with UV ozone to form a uniform film, wherein the spin coating speed is 4500 rpm, the spin coating time is 30 s, and then annealing is performed to completely remove the remaining solution, wherein the annealing temperature is 140° C., the annealing time is 10 min, and after cooling to room temperature, the film is transferred to a glove box filled with nitrogen to obtain a hole transport layer 2 with a thickness of 10 nm;

[0122] 3) preparing the interface modification layer 3: uniformly dropping 50 μL of a CTAB solution dissolved in IPA onto the hole transport layer 2, wherein the solution concentration is 1 mg / mL (denoted as 1-CTAB), and then spin coating the hole transport layer 2 at 4000 rpm for 30 s, and then annealing at 60° C. for 8 min to remove the residual solvent, thereby obtaining the interface modification layer 3;

[0123] 4) Preparation of perovskite light absorbing layer 4: Weigh 260.02 mg of FAI (formamidine hydroiodide), 5.72 mg of MACl (methylammonium chloride), 8.22 mg of MABr (potassium ammonium bromide), 15.59 mg of CsI (cesium iodide), and 10.5 mg of PbI 2 (lead iodide) is 497.89 mg, PbCl 2 (lead chloride) is 16.69 mg, PbBr 2 (Lead bromide) was 22.02 mg, which was dissolved in a mixed solution of 900 μL DMF and 100 μL DMSO to prepare FA 0.90 MA 0.05 CS 0.05 Pb(I 0.90 Cl 0.05 Br0.05 ) 3 Perovskite precursor solution: 65 μL of perovskite precursor solution is dropped on the interface modification layer 3, wherein the spin coating speed is 4500 rpm and the spin coating time is 30 s. During the spin coating process, 200 μL of CB is quickly dropped before the surface becomes turbid. Finally, the prepared film is placed on a hot plate for annealing, wherein the annealing temperature is 100 ° C and the annealing time is 30 min, to obtain a perovskite light absorption layer 4 with a thickness of 400 nm.

[0124] 5) Preparation of electron transport layer 5: After the device is cooled to room temperature, a PCBM solution (20 mg / mL) dissolved in CB is spin-coated on the prepared perovskite light absorption layer 4 at a speed of 4000 rpm for 30 seconds to obtain an electron transport layer 5 with a thickness of 20 nm;

[0125] 6) Preparing a BCP buffer layer 6: Spin-coating a BCP solution (0.5 mg / mL) dissolved in IPA on the prepared electron transport layer 5 at a speed of 8000 rpm for 30 seconds to obtain a BCP buffer layer 6;

[0126] 7) Preparation of top metal electrode 7: At 2×10 -4 Under a pressure of pa, Al is vacuum deposited on the prepared BCP buffer layer 6 to obtain a top metal electrode 7 (the thickness of the top metal electrode 7 is 100 nm), thereby obtaining an inverse perovskite solar cell with buried interface defect passivation.

[0127] Comparative Example 1: No interface modification layer between the hole transport layer and the perovskite light absorbing layer

[0128] The structure of the inverse perovskite solar cell in this comparative example is the same as that in Example 2, except that there is no interface modification layer between the hole transport layer and the perovskite light absorbing layer. The preparation method is as follows:

[0129] 1) treating the transparent conductive substrate 1: using a cleaning agent, deionized water and IPA in sequence to ultrasonically clean an ITO transparent conductive electrode with a thickness of 90 nm for 20 minutes, and then using ultraviolet ozone treatment for 15 minutes, and waiting for subsequent use;

[0130] 2) Preparation of hole transport layer 2: Spin coating the PEDOT:PSS solution on the surface of the pre-ozone treated ITO substrate to form a uniform film, wherein the spin coating speed is 3000 rpm, the spin coating time is 30 s, and then annealing is performed to completely remove the remaining solution, wherein the annealing temperature is 120°C, and the annealing time is 20 min. After cooling to room temperature, transfer to a glove box filled with nitrogen to obtain a hole transport layer 2 with a thickness of 15 nm;

[0131] 3) 50 μL of IPA was dispersed on the hole transport layer 2, followed by spin coating at 4000 rpm for 30 seconds, and finally annealing was performed to remove the residual solvent, wherein the annealing temperature was 70° C. and the annealing time was 5 minutes;

[0132] 4) Preparation of perovskite light absorbing layer 4: 1.2M PbI 2 MAPbI was prepared by dissolving 1.2 M MAI in a mixed solution of 900 μL DMF and 100 mL DMSO. 3 Perovskite precursor solution, 65 μL of perovskite precursor solution is dropped on the product obtained in step 3), wherein the spin coating speed is 4000 rpm, and the spin coating time is 30 s. During the spin coating process, 200 μL of CB is quickly dropped before the surface becomes turbid. Finally, the prepared film is placed on a hot plate for annealing, wherein the annealing temperature is 100° C., and the annealing time is 10 min, to obtain a perovskite light absorbing layer 4 with a thickness of 450 nm;

[0133] 5) Preparation of electron transport layer 5: After the device is cooled to room temperature, a PCBM solution (20 mg / mL) dissolved in CB is spin-coated on the prepared perovskite layer 4 at a speed of 3000 rpm for 30 seconds to obtain an electron transport layer 5 with a thickness of 30 nm;

[0134] 6) Preparing a BCP buffer layer 6: Spin-coating a BCP solution (0.5 mg / mL) dissolved in IPA on the prepared electron transport layer 5 at a speed of 8000 rpm for 30 seconds to obtain a BCP buffer layer 6;

[0135] 7) Preparation of top metal electrode 7: At 2×10 -4 Under a pressure of 10 000 pa, Ag was vacuum deposited on the prepared BCP buffer layer 6 to obtain a top metal electrode 7 (the thickness of the top metal electrode 7 was 100 nm), thereby obtaining an inverse perovskite solar cell.

[0136] Performance Testing

[0137] The perovskite solar cells obtained in Comparative Example 1 and Examples 1-7 were subjected to a photoelectric conversion performance test under sunlight irradiation (according to GB / T 34160-2017), and the results are shown in Table 1.

[0138] Table 1 Performance parameter values ​​of perovskite solar cells corresponding to comparative examples and examples

[0139]

[0140]

[0141] The JV curves of the inverse perovskite solar cells obtained in Comparative Example 1 and Example 2 are shown in Figure 3 , through Table 1 and Figure 3 It can be seen that the J of each device after CTAB and CTAC optimization SC and V OC All of them have been improved to varying degrees, and the PCE has increased significantly. Among them, 0.7-CTAB is the champion device, J SC Increased to 22.50mA / cm 2 , V OC Boosted to 0.95 V, the FF is 81.12% and the best PCE is 17.30%.

[0142] The SEM images of the inverse perovskite solar cells obtained in Comparative Example 1 and Example 2 are shown in Figure 4 It can be known that the present invention uses interface-modified organic compounds to enhance the conductivity of the hole transport layer and modify the lower surface of the perovskite light-absorbing layer, which can improve the perovskite crystallization process, reduce the surface roughness of the perovskite light-absorbing layer, and passivate and reduce interface defects, so as to achieve the purpose of enhancing the photoelectric performance and long-term stability of the battery device.

[0143] The water contact angle images of the hole transport layer of the inverse perovskite solar cell obtained in Comparative Example 1 and Example 2 are shown in FIG. Figure 5 It can be seen that the water contact angle of the hole transport layer after CTAB modification is significantly increased, and the hydrophobicity is enhanced. Therefore, the enhanced hydrophobicity is conducive to the nucleation and growth of the perovskite film crystallization, promotes the improvement of the overall performance, and also inhibits the corrosion effect of water vapor on the device.

[0144] The unpackaged devices obtained in Comparative Example 1 and Example 2 were placed in an indoor environment with a humidity of 60-70% RH and a temperature of 25°C. The efficiency was tested every 50 hours and a normalized image was plotted. The comparison of the long-term stability test results of the unpackaged devices obtained in Comparative Example 1 and Example 2 at room temperature is shown in FIG. Figure 6 It can be seen that under the conditions of humidity 60-70% RH and temperature of 25°C, the CTAC-modified device showed enhanced stability and maintained 80% of the initial efficiency after 400h storage, indicating that the long-term stability of the battery device has been improved.

[0145] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. An inverse perovskite solar cell with buried interface defect passivation, characterized in that: There is an interface modification layer between the hole transport layer and the perovskite light absorbing layer; The material of the interface modification layer is an organic compound containing a hydrophobic long carbon chain, a positively charged amino group and a negatively charged halogen functional group.

2. The inverted perovskite solar cell with buried interface defect passivation according to claim 1, characterized in that: The material of the interface modification layer is hexadecyltrimethylammonium bromide or hexadecyltrimethylammonium chloride.

3. The inverse perovskite solar cell with buried interface defect passivation according to claim 1, characterized in that: It includes from bottom to top: a transparent conductive substrate, a hole transport layer, an interface modification layer, a perovskite light absorption layer, an electron transport layer, a BCP buffer layer and a top metal electrode.

4. The inverted perovskite solar cell with buried interface defect passivation according to claim 3, characterized in that: The transparent conductive substrate comprises indium tin oxide or fluorine-doped tin oxide; and / or The material of the hole transport layer includes one of MeO-2PACz, PEDOT:PSS and Me-4PACz; and / or The material structure of the perovskite light absorbing layer is ABX3, where A is CH3NH3 + 、NH2CH=NH2 + and Cs + One of the following; B is Pb 2+ and Sn 2+ One of the following; X is Cl - Br - and I - One of; and / or The material of the electron transport layer is one of PCBM and fullerene.

5. The inverted perovskite solar cell with buried interface defect passivation according to claim 3, characterized in that: The BCP buffer layer is bathocuproin; and / or The material of the top metal electrode is one of gold, silver, copper and aluminum.

6. The buried interface defect passivated inverse perovskite solar cell according to claim 3, characterized in that: The thickness of the transparent conductive substrate is 80-100 nm, the thickness of the hole transport layer is 10-20 nm, the thickness of the perovskite light absorption layer is 400-500 nm, the thickness of the electron transport layer is 20-40 nm, and the thickness of the top metal electrode is 80-100 nm.

7. A method for preparing an inverse perovskite solar cell with buried interface defect passivation according to any one of claims 1 to 6, characterized in that: The following steps are involved: 1) Preparing a hole transport layer on a transparent conductive substrate; 2) preparing an interface modification layer on the hole transport layer; 3) preparing a perovskite light absorbing layer on the interface modification layer; 4) preparing an electron transport layer on the perovskite light absorbing layer; 5) preparing a BCP buffer layer on the electron transport layer; 6) Preparing a top metal electrode on the BCP buffer layer.

8. The method for preparing a trans-perovskite solar cell with buried interface defect passivation according to claim 7, characterized in that: In step 1), the method for preparing the hole transport layer on the transparent conductive substrate is: coating the material of the hole transport layer on the transparent conductive substrate and performing annealing treatment.

9. The method for preparing a trans-perovskite solar cell with buried interface defect passivation according to claim 7, characterized in that: In step 2), the method for preparing the interface modification layer on the hole transport layer is: dissolving the material of the interface modification layer in an organic solvent, coating the layer on the hole transport layer, and performing annealing treatment.

10. The method for preparing a trans-perovskite solar cell with buried interface defect passivation according to claim 9, characterized in that: In step 2), after the material of the interface modification layer is dissolved in an organic solvent, the concentration of the material of the interface modification layer in the obtained solution is 0.4-2 mg / mL; and / or The organic solvent includes one of dimethyl sulfoxide, N,N-dimethylacetamide, isopropanol and chlorobenzene.

Citation Information

Patent Citations

  • Perovskite solar cell with double surfactant modification layers

    CN112133829A

  • Carbon-based perovskite solar cell without hole transport layer and preparation method thereof

    CN118434174A